Parenting styles of the Kadazandusun community in rural areas of Sabah in ensuring child’s success in school - Rosy Talin; Sabariah Sharif; Soon Singh Bikar Singh; Prescylla Kiok (MJSSH, 2021)
Today, many KadazanDusun children who live in rural areas, whose parents are without educational background and earn a living as farmers, have successfully entered public tertiary level education institutions (IPTA) or private tertiary level education institutions (IPTS). This development has prompted this study to identify the parenting styles involved in ensuring the success of children in school and thus succeeding in furthering to tertiary level. For data collection, this study choses the qualitative approach. Thus, to obtain the required data, interviews were carried out with parents who have more than one child studying at IPTA/IPTS, self-employed in their hometown and had no opportunity to formal education. The respondents were chosen through purposive and snowball selection. The findings show that both authoritarian and authoritative parenting styles are practiced by the KadazanDusun parents in ensuring that children are successful in school. The children who were also interviewed agreed these styles are practiced because of the difficulties in the parents’ lives due to the lack of good education. Therefore, the parents want to ensure their children to succeed in their education for a better future. The parents do not want their economic problems which they are facing now to be inherited by their children.